Absolute humidity, relative humidity: which is more important in representing severity of electrostatic discharge. Issue 23 (1st November 2013) - Wan, F.; Ge, J.‐X.; Pommerenke, D.
Abstract : Humidity is a very important factor in representing the severity of electrostatic discharge (ESD). Low humidity indicates high risk of ESD problems; high humidity indicates low risk of ESD problems. Both relative humidity and absolute humidity can represent the level of humidity: which one is more important? The reported measurement result shows that relative humidity is more important in the discharge phase. The qualitative analysis is given.